2021
DOI: 10.3390/nano11112802
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Strategy for Enhancing the Biomass Growth and Lipid Accumulation of Chlorella sp. UJ-3 Using Magnetic Fe3O4 Nanoparticles

Abstract: In this study, magnetic Fe3O4 nanoparticles (NPs) were used as an effective enhancer to increase the biomass and total lipid production of Chlorella sp. UJ-3. It was found that the biomass of algal cells increased significantly when they were exposed to low concentrations of Fe3O4 NPs (20 mg/L), while the best total lipid content of algal cells was achieved when they were exposed to high concentrations of Fe3O4 NPs (100 mg/L). Therefore, we established a strategy to promote the growth and lipid accumulation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 48 publications
(63 reference statements)
0
7
0
Order By: Relevance
“…There are cases where low concentrations of nanoparticles have shown positive effects, while high concentrations have exerted negative effects ( Pádrová et al, 2015 ; Cepoi et al, 2020 ). In other cases, however, an inverse relationship has been revealed ( Wang et al, 2021 ). In the context of nanoparticle effects on organisms, the notion of low and high concentrations refers more to the effects produced rather than the quantity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are cases where low concentrations of nanoparticles have shown positive effects, while high concentrations have exerted negative effects ( Pádrová et al, 2015 ; Cepoi et al, 2020 ). In other cases, however, an inverse relationship has been revealed ( Wang et al, 2021 ). In the context of nanoparticle effects on organisms, the notion of low and high concentrations refers more to the effects produced rather than the quantity.…”
Section: Discussionmentioning
confidence: 99%
“…A similar response was found under the growth conditions of mixotrophic Chlorella sp . UJ-3 in the presence of low concentrations of Fe 3 O 4 nanoparticles in nutrient medium ( Wang et al, 2021 ). In the case of AuNPs of both sizes, lipid content in biomass was significantly higher, but the effect was not concentration–dependent.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have shown the importance of cultivation conditions for microalgal growth and lipid accumulation. Nutrients [ 19 , 20 ], high salinity [ 21 , 22 ], metal ions [ 23 ], light intensity, temperature, pH, and abiotic/biotic treatments are regarded as critical parameters for microalgal growth and lipid accumulation. This review presents updated research on Chlorella biomass and lipid production, published mainly in the last five years, and discusses the subsequent progress and perspectives.…”
Section: Introductionmentioning
confidence: 99%
“…in POME as medium was obtained in the optimal condition of 10.9% CO 2 and 9963.8 lux of light intensity through central composite designs [3]. The microalgal growth and lipid production were enhanced by the addition of phytohormone indole-3-butyric acid (IBA) [2], ferroferric oxide (Fe 3 O 4 ) nanoparticles [29], sodium nitrate (NaNO 3 ) [30], glycerol [31], etc. Additionally, the producing biomass microalgal CO 2 fixation can be used to produce specific components that can be refined as high-value byproducts to realize the economic sustainability [32].…”
Section: Introductionmentioning
confidence: 99%